Comparative study of different alloys during thermal debind-ing of powder injection molded parts - El-Garaihy, Waleed; Nassef, Ahmed; El-Hadek, Medhat (International Journal of Engineering and Technology, 2016)
Powder injection molding (PIM) is an interesting technique and address of research, in which a thermoplastic polymeric material is used to form the powder into the desired shape in a closed die. Binders have a crucial importance in the powder metallurgy technology as they play a vital role to provide efficient powder agglomeration and/or lubrication during shaping. At the same time, they have to be easily removed from the compacts during initial stages of sintering, using debinding process, without any damaging effect for the base material. Thermal debinding is a vital process requiring somewhat elevated temperatures to remove binder from the compact. In the current study, an investigation has been made about the effect of process variables on the debinding of injection molded pieces, by melt wicking. The debinding process was performed at temperatures ranging from 160- up to-200Â°C for a time duration varying from 1-up to-27 hours. All powders used in injection molding feedstock have an inherent packing porosity. Several types of alloy powders (Carbonyl iron steel, Nickel aluminide, and 316L stainless powders), with various size distributions, particle shapes, and materials are adopted to define the influence on binder incorporation resulted from this inherent porosity. Results revealed that the increase of debinding time or decrease in the wicking powder (alumina) particle size lead to an increase in the thickness of the adhered layer of alumina. When the wicking powder is very fine (0.3 mm) or has a wide particle size range (<10 mm), it becomes more dense and its debinding efficiency is decreased. At high debinding temperatures (200 Â°C) the rate of binder evaporation and removal increased, which leads to decreasing the cohesion of the samples yielding a shape distortion. In addition, the effect of the wicking powder (Al2O3) sizes and debinding time on the binder weight loss percentage after debinding process for FeOX, Ni3Al, and 316L has been investigated.